PERSEPSI ANAK TERHADAP PESAN DALAM FILM KARTUN UPIN & IPIN DI KALANGAN ANAK SD NEGERI 040 HUTA GODANG MUDA, KECAMATAN SIABU, KABUPATEN MANDAILING NATAL - Suaibatul Aslamiah; Rita Vinolia Aruan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
This study aims at finding out what perceptions and messages the children get when watching Upin & Ipin shows. This is a descriptive qualitative research. The population of this study is the students grade V and VI in Public Elementary School 040 Huta Godang Muda, Siabu Subdistrict, Mandailing Natal Regency. The results of this study describe the meaning of the message, basically the children reveal that Upin & Ipin are good, polite, like to help people in distress, please help, protect the environment, funny, honest, friendly and most importantly they already understand the messages the message conveyed in the film Upin & Ipin. Upin & Ipin way of speaking Also good and polite, Upin & ipin's behavior is also good and can be replicated in everyday life.